2013
DOI: 10.1007/s10653-013-9511-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of minor and trace elements with mineralogical constituents of urinary stones: A hard nut to crack in existing studies of urolithiasis

Abstract: The role of metals in urinary stone formation has already been studied in several publications. Moreover, urinary calculi can also be used for assessing exposure of humans to minor and trace elements in addition to other biological matrices, for example, blood, urine, or hair. However, using urinary calculi for biomonitoring of trace elements is limited by the association of elements with certain types of minerals. In this work, 614 samples of urinary calculi were subjected to mineralogical and elemental analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 26 publications
5
15
1
1
Order By: Relevance
“…Significant differences (p \ 0.001) were found for all tested elements except for K (p = 0.267). Similar results were found in our previous work with exception for Cr and Se where no significant difference was detected (Kuta et al 2013(Kuta et al , 2012. This is in agreement with work of Bazin and Giannossi (Bazin et al 2007;Giannossi et al 2013) who reported higher contents of metal elements in calcium oxalates (whewellite and weddellite) compared to uric acid stones.…”
Section: Contents Of Elements In Whewellite and Uric Acid Stonessupporting
confidence: 93%
See 4 more Smart Citations
“…Significant differences (p \ 0.001) were found for all tested elements except for K (p = 0.267). Similar results were found in our previous work with exception for Cr and Se where no significant difference was detected (Kuta et al 2013(Kuta et al , 2012. This is in agreement with work of Bazin and Giannossi (Bazin et al 2007;Giannossi et al 2013) who reported higher contents of metal elements in calcium oxalates (whewellite and weddellite) compared to uric acid stones.…”
Section: Contents Of Elements In Whewellite and Uric Acid Stonessupporting
confidence: 93%
“…Giannossi reported higher content of Zn in uric acid and cystine stones (Giannossi et al 2013), which is in contrast with our results and work of Bazin (Bazin et al 2007) where higher content of Zn was found in oxalates. On the other hand, Bazin and Giannossi (Bazin et al 2007;Giannossi et al 2013) detected higher representation of Cu in calcium-containing stones, which is not in agreement with results of our previous study where significantly higher content of Cu was found in uric acid stones compared to phosphates and oxalates (Kuta et al 2013).…”
Section: Contents Of Elements In Whewellite and Uric Acid Stonescontrasting
confidence: 59%
See 3 more Smart Citations